Psychosocial Problems of Homeless Sexual Minority Youths and Their Heterosexual Counterparts - Gattis, Maurice (2010)
Abstract The purpose of this dissertation was to better understand the psychosocial problems: mental health problems, substance use problems, and sexual risk behaviors) and the associated contextual risk factors by comparing homeless sexual minority youths with their heterosexual counterparts. This study used an ecological perspective: Bronfenbrenner, 1989) and a risk and protective factors framework: Hawkins, Catalano, & Miller, 1992) to identify contextual risk factors at the microsystem, mesosystem, and macrosystem levels that are associated with the psychosocial problems of homeless sexual minority and homeless heterosexual youths. Individuals aged 16-24 were recruited from three drop-in programs serving homeless youths in downtown Toronto: N=147). Structured interviews were conducted with each participant. Bivariate analyses indicated statistically significant differences between homeless sexual minorities: n=66) and their heterosexual counterparts: n=81) regarding mental health, substance use and sexual risk behaviors, as well as contextual factors such as peers, family communication, stigma, and discrimination with sexual minority youths faring more poorly. Results of multiple regression analyses indicated that sexual identity moderated the relationship between negative peers and three psychosocial behaviors: sexual risk behaviors, condom use and substance use. Among sexual minorities, having peers who engaged in negative behaviors was associated with increased risky behaviors, but for homeless heterosexual youths, there was no effect between negative peers and their sexual risk behaviors and substance use. Results also indicated that sexual identity did not moderate the relationship between other contextual factors: i.e., family communication, stigma, or discrimination) and psychosocial outcomes such as mental health, substance use, and sexual risk behaviors. Understanding the nature and direction of the differences between homeless sexual minority youths and their heterosexual counterparts is an important first step in reducing disparities regarding negative outcomes of this population of youths